Detection and Characterization of Autoantibodies to Neuronal Cell-Surface Antigens in the Central Nervous System - van Coevorden-Hameete, Marleen H.; Titulaer, Maarten J.; Schreurs, Marco W. J.; de Graaff, Esther; Sillevis Smitt, Peter A. E.; Hoogenraad, Casper C. (Frontiers in Molecular Neuroscience, 2016)
Autoimmune encephalitis (AIE) is a group of disorders in which autoantibodies directed at antigens located on the plasma membrane of neurons induce severe neurological symptoms. In contrast to classical paraneoplastic disorders, AIE patients respond well to immunotherapy. The detection of neuronal surface autoantibodies in patients’ serum or CSF therefore has serious consequences for the patients’ treatment and follow-up and requires the availability of sensitive and specific diagnostic tests. This mini-review provides a guideline for both diagnostic and research laboratories that work on the detection of known surface autoantibodies and/or the identification of novel surface antigens. We discuss the strengths and pitfalls of different techniques for anti-neuronal antibody detection: 1) Immunohistochemistry and immunofluorescence on rat/ primate brain sections, 2) Immunocytochemistry of living cultured hippocampal neurons, 3) Cell Based Assay (CBA). In addition, we discuss the use of immunoprecipitation and mass spectrometry analysis for the detection of novel neuronal surface antigens, which is a crucial step in further disease classification and the development of novel CBAs.